1996
DOI: 10.1046/j.1365-2958.1996.6281349.x
|View full text |Cite
|
Sign up to set email alerts
|

An alternative PII protein in the regulation of glutamine synthetase in Escherichia coli

Abstract: SummaryThe P II protein has been considered pivotal to the dual cascade regulating ammonia assimilation through glutamine synthetase activity. Here we show that P II , encoded by the glnB gene, is not always essential; for instance upon ammonia deprivation of a glnB deletion strain, glutamine synthetase can be deadenylylated as effectively as in the wild-type strain. We describe a new operon, glnK amtB, which encodes a homologue of P II and a putative ammonia transporter. We cloned and overexpressed glnK and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
291
3
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(312 citation statements)
references
References 66 publications
16
291
3
2
Order By: Relevance
“…This protein is obviously crucial for intracellular signal transduction. Yet, it lacked control on the average adenylylation state of GS even in the absence of its paralogue GlnK (55). We found that, especially because the ATase is an ambiguous enzyme, altered expression of total PII protein should not affect the steady-state activity of GS, unless the ratio of PII͞PII-UMP were to change in parallel.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This protein is obviously crucial for intracellular signal transduction. Yet, it lacked control on the average adenylylation state of GS even in the absence of its paralogue GlnK (55). We found that, especially because the ATase is an ambiguous enzyme, altered expression of total PII protein should not affect the steady-state activity of GS, unless the ratio of PII͞PII-UMP were to change in parallel.…”
Section: Discussionmentioning
confidence: 83%
“…The authors varied the total concentration of PII. The nonadenylylated GS concentration was completely insensitive to changes in total PII protein level, also when the paralogue of PII, GlnK (54), was absent (55).…”
Section: Gs In E Colimentioning
confidence: 99%
“…Many authors have pointed out that the bicyclic structure of the cascade serves to integrate signals of the nitrogen (via glutamine) and carbon (via α -KG) status of the cell [11, 25, 30]. Westerhoff and colleagues have proposed [3, 31] that the combination of PII and its homologue GlnK enables the cell to precisely adjust its strategy for GS regulation in response to varying external ammonium concentrations. They find that the combined regulation of GS–GOGAT and GDH allows E. coli to maintain a roughly constant rate of nitrogen influx regardless of ammonium levels [5].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequence encoding GlnK was polymerase chainreaction (PCR) amplified from template plasmid pWVH149 (van Heeswijk et aL, 1996) using a forward primer (5'-AATGGATCCCATATGAA-GCTGGTGACCGTG-3') which introduced a convenient NdeI restriction site (CATATG) at the start and the M13 primer (5'-GTAAAACGCGACGGCCAGT-3'). PCR using standard conditions was carried out with Expand polymerase (Boehringer Mannheim).…”
Section: Construction Of Plasmid Pnvi02mentioning
confidence: 99%
“…GlnK is a signal-transduction protein which has recently been implicated in the regulation of glutamine synthetase (GS) in Escherichia coli (van Heeswijk et al, 1996). It is a homotrimer with subunits of 112 amino acids and has 67% sequence identity with the Pxi protein, whose role in the regulation of GS in enteric bacteria is well studied (Merrick & Edwards, 1995).…”
Section: Introductionmentioning
confidence: 99%